Partisan Bias and Information Discounting in Economic Judgments. Issue 3 (6th September 2013) - Ramirez, Mark D.; Erickson, Nathan
<x xml:space="preserve">Abstract</x> Research shows that partisanship biases people's views about the economy. Yet, there is little understanding of the factors, if any, that might mitigate the influence of partisanship on these judgments or the effect of partisanship on metacognitive judgments. This study uses an experimental design to show that partisanship continues to bias economic judgments even when subjects receive direct and neutral information about specific aspects of the economy. Moreover, it extends our understanding of partisan bias by showing it has a direct effect on people's metacognitive assessments of their own attitudes—particularly the degree of uncertainty people have in their own economic judgments. However, it appears that people are aware of the conflict between their partisan‐based judgment and economic information since we observe increases in economic uncertainty when information is counter to a subject's partisan predisposition. The results provide new insight into the extent of partisan bias and the difficulty of countering partisan‐based judgments.